CHRONIC VIRAL HEPATITIS IN CHILDREN - SOCIO-ECONOMIC IMPLICATIONS IN ROMANIA - Irina Dijmărescu; Alexandra Coroleucă; Alexandru Dinulescu; Adrian Dumitru Dijmărescu; Lorenza Forna; Daniela Păcurar; Cristina Adriana Becheanu (Romanian Society of Oral Rehabilitation, 2024)
Background: This research approaches chronic viral hepatitis in children from a multidisciplinary point of view, the disease being considered a great burden. (2) Methods: We conducted a 4-year observational prospective study, analyzing socio-economic status of pediatric patients diagnosed with chronic viral hepatitis B or C. (3) Results: In total, 159 patients were included. Only 66% of school-aged children were attending classes. Regarding the monthly income per family, 49% had less than 1000 RON (5 RON = 1$), of which 17% had no income. The average years of study for mothers was 7.8, for fathers it was 8.2. For 17 % of children, at least one of the parents was illiterate, for 5.6 %, both. For one third of patients, both parents were unemployed. Water facilities or sewerage were not available for 38.4% of children, and 32 % used personal objects (scissors, nail clippers) in common. (4) Conclusions: The socio-economic level can have a significant impact on disease epidemiology (infectiousness) and access to treatment, and it is tightly related to educational level and access to information, which are critical factors in disease prevention through general and specific measures and in disease management (treating infected patients and limiting the transmission).